Isolation and characterisation of endophytic bacteria from Nam-nam plants (Cynometra cauliflora) / Rabiatul Adawiyah Mohamad Khalil - Mohamad Khalil, Rabiatul Adawiyah (2022)
Endophytic bacteria live within the living plants by colonizing the internal tissue of the plants. Mutualistic symbiosis between these microorganisms and plants works in a way that the bacteria benefit from plants because of nutrients availability whereas plants receive benefits of growth enhancement and stress reduction from the bacteria. Nam-nam plant (Cynometra cauliflora), a small tree with thick and branched stems is indigenous to the eastern Peninsular Malaysia. This tree has the potential to be commercialized for its medicinal properties. This study aimed to isolate endophytic bacteria from different parts of Nam-nam plants (C. cauliflora) such as leaves, stems and roots. The isolated bacterial endophytes were screened for biochemical characterisation before the extraction of secondary metabolite using ethyl acetate. The extracts were tested for antimicrobial activity as well as production of indole-3-acetic acid (IAA). Molecular characterisation via analysis of 16S gene sequencing was also performed to identify the isolates with good antimicrobial activity and high production of IAA. A total of 33 endophytic bacteria were isolated from roots, stems and leaves of Nam-nam plants comprising of 6 Gram positive and 27 Gram negative bacteria. A total of seven bacterial endophyte extracts showed antimicrobial activity against pathogenic bacteria in which R1L3 and TKL2 extracts exhibited significant activity against Bacillus cereus, Escherichia coli and Proteus vulgaris. Production of IAA was exhibited by 15 isolates wherein R1S4 produced the highest IAA (20.62 μg/mL), followed by TKS2 (14.44 μg/mL) and R1S5 (12.05 μg/mL). Analysis of 16S gene sequence revealed that TKL2, TKS2/R1L3 and R1S4/R1S5 belonged to the genera of Methylobacterium, Mycobacteroides and Sphingomonas, respectively. The findings from this study showed that Nam-nam plants harboured endophytic isolates with the potential to be established in the future, especially as a source of natural compounds that can be used to develop new anti-infection agents. This is the first study to report on antimicrobial activity against pathogenic bacteria and IAA production by endophytic bacteria from the Nam-nam plants.